2005
DOI: 10.1177/107424840501000404
|View full text |Cite
|
Sign up to set email alerts
|

Sarcoplasmic Reticulum Adenosine Triphosphatase Overexpression in the L-type Ca2+ Channel Mouse Results in Cardiomyopathy and Ca2+-Induced Arrhythmogenesis

Abstract: Despite previous reports of improved cardiac function in heart failure models after SERCA intervention, our results advocate the need to elucidate the involvement of augmented Ca(2+) cycling in arrhythmogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…When these mice are interbred with mice overexpressing a skeletal muscle form of the sarcoplasmicendoplasmic reticulum Ca 2+ ATPase (SERCA1a) they develop more marked hypertrophy, increased CaMKII expression, action potential prolongation, afterdepolarizations and arrhythmias [50]. On the other hand, these investigators found that a known CaMKII phosphorylation site on the SERCA regulatory protein phospholamban (threonine 17) was hypo-phosphorylated, suggesting that other uncharacterized compensatory mechanisms are active in this model.…”
Section: Proarrhythmic Electrical Remodelingmentioning
confidence: 99%
“…When these mice are interbred with mice overexpressing a skeletal muscle form of the sarcoplasmicendoplasmic reticulum Ca 2+ ATPase (SERCA1a) they develop more marked hypertrophy, increased CaMKII expression, action potential prolongation, afterdepolarizations and arrhythmias [50]. On the other hand, these investigators found that a known CaMKII phosphorylation site on the SERCA regulatory protein phospholamban (threonine 17) was hypo-phosphorylated, suggesting that other uncharacterized compensatory mechanisms are active in this model.…”
Section: Proarrhythmic Electrical Remodelingmentioning
confidence: 99%
“…MA1-980), and monoclonal anti-calsequestrin antibody (1:2,500, PA1-913). Calsequestrin was used as an internal protein content reference (30,47). Membranes were then washed and incubated with secondary antibody for 1 h at room temperature [1:100,000 for c-myc (i.e., SERCA1) and 1:50,000 for SERCA2 and calsequestrin] (goat antimouse horseradish peroxidase-conjugated antibody, Pierce).…”
Section: Methodsmentioning
confidence: 99%
“…SERCA plays a major role in the regulation of intracellular Ca 2+ and directly affects myocardial function. Increase or decrease in SERCA activity may lead to heart failure and arrhythmia ( 17 ). Moreover, the reduced activity or expression of SERCA2a may lead to myocardial cell dysfunction ( 3 ).…”
Section: Discussionmentioning
confidence: 99%